Dynamic nature of intracranial venous sinuses in idiopathic intracranial hypertension. Issue 1 (February 2020) - Nicholson, Patrick; Lenck, Stéphanie; Kucharczyk, Walter; Mendes-Pereira, Vitor
There is increasing interest in venous sinus stenting in patients with idiopathic intracranial hypertension who are refractory to medical therapy. Often the transverse sinus stenoses are bilateral, however, and there is no clear evidence for whether we should stent one or both sides in these patients. Our practice is to first stent one side, and in this brief case report, we demonstrate complete resolution of the contralateral stenosis in one such patient who underwent stenting. Her symptoms also completely resolved, and so this case highlights the dynamic fluctuant nature of the transverse sinuses.